2012
DOI: 10.1194/jlr.m021949
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of diabesity-induced colorectal ontogenesis by omega-3 fatty acids in mice

Abstract: This article is available online at http://www.jlr.org stationary, pluripotent stem cells at the base of the crypt give rise to rapidly proliferating cells that differentiate into postmitotic columnar absorptive colonocytes, mucinsecreting goblet cells, and enteroendocrine cells as they migrate from the crypt base to the surface, followed fi nally by their shedding into the intestinal lumen (reviewed in Ref. 1 ). Several signaling pathways, notably ␤ -catenin/Tcf and hepatocyte nuclear factor (HNF)-4 ␣ , modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 48 publications
4
14
0
Order By: Relevance
“…This suggests that the reverse EMT process, known as mesenchymal-epithelial transition, may have occurred in fat-1 tumor tissues. Consistent with these results, recent studies have demonstrated that breast and colorectal cancer tissues from fat-1 mice display increased levels of E-cadherin expression, which indicates that its expression may be modulated by endogenous n-3 PUFAs (37,38). However, in the present study, the formation of metastases in the lungs or other organ sites in fat-1 and WT mice was not observed (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that the reverse EMT process, known as mesenchymal-epithelial transition, may have occurred in fat-1 tumor tissues. Consistent with these results, recent studies have demonstrated that breast and colorectal cancer tissues from fat-1 mice display increased levels of E-cadherin expression, which indicates that its expression may be modulated by endogenous n-3 PUFAs (37,38). However, in the present study, the formation of metastases in the lungs or other organ sites in fat-1 and WT mice was not observed (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…As noted earlier, we have recently demonstrated that obesity‐associated diabetes leads to distorted colonic morphology and colonic dysplasia (65). Proliferation, differentiation and transduction aspects of intestinal ontogenesis are disturbed in the diabetes‐obese murine model (db/db mice) but are prone to significant amelioration by endogenous n‐3 PUFA provided by crossing db/db mice with fat‐1 mice.…”
Section: Therapeutic and Dietary Implications For Obesity‐related Crcmentioning
confidence: 67%
“…We have recently demonstrated severe alterations in postnatal intestinal ontogenesis of the large intestine in an animal model of hyperinsulinemia‐associated obesity (db/db mice) (65). We demonstrated, in this mouse model, distorted colonic morphology and associated transduction features, all of which might affect colonic dysplasia.…”
Section: Obesity and Colorectal Cancer (Crc)mentioning
confidence: 75%
See 1 more Smart Citation
“…This diet was low (0.5% of dietary energy) in α-linolenic acid (18:3n3), which comprises 1% of fatty acids in corn oil (25). It is possible that this fatty acid imbalance (47) may have contributed to the effects observed for the high-fat diet, as α-linolenic acid has been suggested to be anticarcinogenic (48,49). This possibility warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%